2017
DOI: 10.1111/jace.15038
|View full text |Cite
|
Sign up to set email alerts
|

Microstress in the matrix of a melt‐infiltrated SiC/SiC ceramic matrix composite

Abstract: Microstress in the SiC: Si matrix of a ceramic matrix composite (CMC) has been characterized, using Raman spectroscopy. The matrix of the composite was manufactured using liquid melt infiltration, and has about 20% unreacted free silicon. During the processing of the composite, the unreacted free silicon expands 11 vol % when transforming from liquid to solid. This crystallization expansion creates compressive microstress in the silicon phase of the matrix, which ranges from 2.4 to 3.1 GPa, and tensile microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 28 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Besides, DiGregorio et al [ 90 ] suggested that the Raman shift of the TO mode and LO mode of SiC materials and the residual stress met the following equation: where and were the Raman shift of the TO mode with and without residual stress, respectively, and were the Raman shift of the LO mode with and without residual stress, respectively, σ was the measured residual tensile stress in GPa. This had been proven to be consistent for α and β -SiC [ 93 , 94 , 95 ]. For 3C-SiC ( β -SiC), the TO mode and LO mode for the unstressed state are 796 cm −1 and 973 cm −1 , respectively [ 96 ].…”
Section: Raman Spectroscopy Characterization In Micro/nano-machinimentioning
confidence: 63%
“…Besides, DiGregorio et al [ 90 ] suggested that the Raman shift of the TO mode and LO mode of SiC materials and the residual stress met the following equation: where and were the Raman shift of the TO mode with and without residual stress, respectively, and were the Raman shift of the LO mode with and without residual stress, respectively, σ was the measured residual tensile stress in GPa. This had been proven to be consistent for α and β -SiC [ 93 , 94 , 95 ]. For 3C-SiC ( β -SiC), the TO mode and LO mode for the unstressed state are 796 cm −1 and 973 cm −1 , respectively [ 96 ].…”
Section: Raman Spectroscopy Characterization In Micro/nano-machinimentioning
confidence: 63%
“…There are inherent difficulties in producing these materials, not least of which is controlling the levels of residual stress within the composite. The stresses come as a result of coefficient of thermal expansion mismatch between constituents, intrinsic stresses developed during chemical vapor infiltration, and possibly crystallization expansion of silicon resulting from a significant volume increase in the phase transition from liquid to solid . To capitalize on the vast benefits of CMCs, the full residual stress state must be understood, predicted, and controlled.…”
Section: Introductionmentioning
confidence: 99%
“…To capitalize on the vast benefits of CMCs, the full residual stress state must be understood, predicted, and controlled. Various authors have experimentally determined residual stress states through Raman spectroscopy, X‐ray diffraction, indentation, piezospectroscopic methods, and the common intersection point method . The reported stresses determined through these multiple techniques vary by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials of the type C/SiC and SiC/ SiC are distinguished by low specific gravity, wear resistance, the possibility of the formation of these products of complex shape, in reducing conditions of operation, these composites retain high mechanical properties up to a temperature of 2000°C [87]. The most promising material at present is SiC and SiC-based materials, which allow to obtain the specified combination of properties: high specific strength and rigidity; heat resistance; wear resistance; high thermal conductivity and heat-shielding properties; radiation strength [88]; etc. ; thermal conductivity of 180-200 W/(m • K) (as in Al), in single crystals up to 470 W/ (m • K); working temperaturemore than 1350°C (as in heatresistant steels); melting/decomposing point is 2830°C; resistance in the oxidizing and reducing environment is higher than that of Ti [89].…”
Section: Ceramic and Metal Matrix Compositesmentioning
confidence: 99%